Response of different drip irrigation and fertigation levels on quality and seed yield in fennel (Foeniculum vulgare) - AKASH; GHIYAL, VIKRAM; PANGHAL, V P S; MALIK, T P; YADAV, PREETI; KASWAN, NIKHIL; SINGH, GAGANDEEP; JAKHAR, SOURABH (The Indian Journal of Agricultural Sciences, 2024)
The present experiment was conducted during winter (rabi) seasons of 2021–22 and 2022–23 at Chaudhary Charan Singh Haryana Agriculture University, Hisar, Haryana to study the effect of different drip irrigation and fertigation levels on quality and seed yield in fennel (Foeniculum vulgare Mill.) crop. The experiment was laid out in a split-split plot design in which 2 fennel varieties, viz. HF-143 and Hisar Swarup were grown with 4 levels of different irrigation scheduling, viz. I1, 0.6 IW/CPE (Irrigation water/Cumulative pan evapo-transpiration); I2, 0.8 IW/CPE; I3, 1.0 IW/CPE and I4, 1.2 IW/CPE as main plot treatments and 3 different nitrogen levels i.e. N1, 20 kg/ha; N2, 35 kg/ha and N3, 50 kg/ha as sub-sub plots treatment. A range of nitrogen levels was applied in the experimental field through drip irrigation. It was clear from the study that irrigation scheduled at 1.2 IW/ CPE resulted significantly higher values when irrigated for quality parameters (test weight, seed germination and vigour indices I and II) and seed yield, which was statically at par with 1.0 IW/CPE. Maximum seed yield (15.5 g/plant), test weight (5.0 g), seed germination (84.0%) and vigour indices I (1,518.98) and II (281.13) were significantly recorded at nitrogen levels 50 kg/ha. Higher seed’s yield and quality parameters were recoded in variety HF-143 than Hisar Swarup. Based on the current study, it can be concluded that in the western region of Haryana, fennel variety HF-143 obtains better results, both in terms of quality and yield parameters when grown at irrigation scheduling IW/CPE 1.0 with 50 kg/ha of nitrogen level.